Microbial exploration of the origin of the Pandeglang cocoa plant (Theobroma cacao L.) rhizosphere as potential biofertilizer - N Nurmayulis; Fitria Riany Eris; Dewi Hastusi; Abdul Hasyim Sodiq; Yus Rama Denny; Dwi Ningsih Susilowati (Journal of Degraded and Mining Lands Management, 2021)
This study aimed to determine the ability of microorganisms originating from the root ecosystem (Rhizosphere) of cocoa (Theobroma cacao L) as a potential superior to biological agents. For the experiment, soil samples were observed from the rhizosphere of cocoa plants in Pandeglang Regency. At this stage, the research was focused on finding out the extent of microbe screening results from cocoa rhizosphere soil in producing phytohormones. The results from the initial selection showed a population of Azotobacter 2.8 x 105 cfu/mL, a population of Azospirillium of 0.3 x 102 cfu/mL, and a population of Phosphate-solubilizing bacteria (PSB) 4.1 x 107 cfu/mL. In the hemolysis test conducted for 9 isolates, only 1 isolate showed a negative result. From the test of the ability to produce phytohormones showed respectively from the highest values were IAA 5.467 mg/L, gibberellin 3.768 mg/L, zeatin 1.321 mg/L, and kinetin 0.886 mg/L. The land rhizosphere of Pandeglang cocoa plant had superior potential microbes which could be used as biological fertilizers.